(untitled) (Journal of Medicine, 2011)
Use of dentures is not an uncommon practice. Swallowing of such dentures can give rise to variable symptoms ranging from chest pain, dysphagia, oesophageal perforation, and erosion of a vessel leading to haemorrhage or rarely gastric outlet obstruction. Here we present a case of 62 year old man presenting with chest pain, dyspepsia, early satiety leading to occasional self induced vomiting . Upper GI endoscopy was performed which revealed an impacted denture in duodenum. Keyword: Impacted denture; Chest pain; Upper GI Endoscopy; Bangladesh. DOI: 10.3329/jom.v12i1.6933 J Medicine 2011; 12 : 58-60